P-275 Inspiring leadership leading self: leading with others in a palliative care setting. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Wylie, Fiona; O'Neill, Claire; Miller, Jane; Jackson, Susan
Abstract : Background: It is recognised within palliative care (PC) that Band 6 Clinical Nurse Specialists (CNS) are working in a time of organisational change with increasing complexity around their specialist role (NHS Education for Scotland 2006). CNSs, in particular newly appointed staff, have reported feeling more vulnerable and stressed and struggling to cope to deliver the same quality of care to patients and their families. To support the above scenario an NHSGGC PC Leadership Steering Group was established in partnership with NES Leadership Unit. Aims: Provide a safe space for participants to share and learn from each other Provide a training programme which embeds the values, behaviours and attitudes of leadership skills Provide a foundation to support greater successional planning throughout palliative care (Scottish Government, 2013; Scottish Government, 2015) Increase participants' knowledge and understanding of quality improvement (QI) methodology supporting individual QI action plans. Methods: The development of a 12 month leadership programme based on needs of the participants, open to all Band 6 PC CNSs working within NHSGGC acute and hospice care settings, was established. The programme includes a leadership resource folder, ongoing staff support, feedback to participants utilising 360 degree review and Myers Briggs, provision of mentoring and action learning sets and evaluation process. Results: Interim feedback to date 10 CNSs signed up. To date participants have attended a launch day and two masterclasses held on: Understanding Myers Briggs and working with differences; Understanding Quality Improvement methodology. All participants have received '360 review process' feedback based on the NHS Scotland Leadership Qualities Framework helping to inform their PDP. All have participated in an action learning set. Three further masterclasses are built around learning needs of the cohort. Conclusion: Feedback to date has highlighted the importance of this programme in addressing a need, focusing on developing leadership skills for a capable, sustainable workforce. Further evaluation is embedded within this programme.